Kinetics and Mechanism of Oxidation of Isobutylamine and 1,4-Butanediamine by Potassium Ferrate - Shan Jinhuan; Yang Yafeng (E-Journal of Chemistry)
The kinetics of oxidation of isobutylamine and 1,4-butanediamine by home-made potassium ferrate(VI) at different conditions has been studied spectrophotometrically in the temperature range of 288.2 -303.2 K. The results show first order dependence on potassium ferrate(VI) and on each reductant. The observed rate constant (kobs) decreases with the increase of [OH-], the reaction was negative fraction order with respect to [OH-]. A plausible mechanism was proposed and the rate equations derived from the mechanism can explain all the experimental results. The rate constants of the rate-determining step and the thermodynamic activation parameters were calculated.